South Atlantic passive margin evolution: a thermochronology case study from the Rio de Janeiro-Três Rios section, SE Brazil - Gezatt, Julia Neri (2021)
The southeastern Brazilian passive margin records a complex post-rift evolution, with two parallel high-elevation features formed after the opening of the South Atlantic. We applied apatite fission track (AFT) and U–Th/He (AHe) low temperature thermochronology to constrain the thermo-tectonic history of the Serra do Mar escarpment in the area of Rio de Janeiro state. New AFT central ages for basement areas collected from a N–S transect orthogonal to the shoreline between the cities of Rio de Janeiro and Trˆes Rios, range between 98.5 ±5.3 and 54.1 ±4.2 Ma, with mean track lengths between 12.34 ±0.40 and 14.63 ±0.17 μm. Uncorrected AHe ages lie between 68.1 ±5.9 and 60.2 ±7.3 Ma and are consistent with AFT results. Inverse thermal history models constrained by AFT and AHe data imply the earliest cooling onset from the Barremian (Early Cretaceous), with steady rates more common for samples closer to coastal areas. Maximum depths of denudation are between 2.5 and 4.5 km. Published thermochronological data from adjacent areas combined with the new results show a seemingly simpler post-rift evolution for the area, although suggesting structural control of age distribution and exhumation.